Human sperm cryopreservation and reactive oxygen species (ROS) production - Mazzilli, F; Rossi, T; Sabatini, L; Pulcinelli, F M; Rapone, S; Dondero, F; Gazzaniga, P P (Acta Europaea fertilitatis, 1995)
The aim of this work was to establish whether cryopreservation procedure can trigger the production of Reactive Oxygen Species (ROS) in selected sperm populations. Semen samples were obtained from 45 subjects attending our Department of Medical Pathophysiology. Motile sperm suspensions were obtained by swim-up in Tyrode's salt solution. After dilution with TEST yolk buffer freezing medium, they were cryopreserved in liquid nitrogen. In addition to motility assessment, in basal and freeze/thaw conditions ROS detection and the Hypoosmotic Viability Test were also carried out. In 19 subjects (42.2%) there was already evidence of ROS production prior to cryopreservation, which increased after thawing. In 9 subjects (20.0%) there was no ROS production prior to cryopreservation, however, after freezing/thawing we detected evidence of the presence of ROS. It seems, therefore, that cryoprocedure can indeed provoke or increase ROS production in some semen samples. In ROS producing subjects, the post-show recovery of sperm motility and vitality was significantly lower compared to ROS-free subjects. This was probably due to damage by oxidative stress leading to lipid peroxidation of the sperm membrane. Moreover, in some ejaculates, ROS overproduction or scavenger system failure can be regarded as a cryopathogenetic factor affecting "sperm quality" recovery.